Neolignans from Aniba citrifolia - Trevisan, Ligia M.V. [UNESP]; Yoshida, Massayoshi [UNESP]; Gottlieb, Otto R. (Elsevier B.V., 1984)
The trunk wood of Aniba citrifolia contains hydrobenzofuranoid and bicyclo[3.2.1]octanoid neolignans. © 1984.
Keywords: Aniba citrifolia; Lauraceae; Neolignans